2016
DOI: 10.3390/su8050481
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Household Yard Area Dynamics in the City of San Juan Using Multi-Scalar Social-Ecological Perspectives

Abstract: Urban sustainability discourse promotes the increased use of green infrastructure (GI) because of its contribution of important ecosystem services to city dwellers. Under this vision, all urban green spaces, including those at the household scale, are valued for their potential contributions to a city's social-ecological functioning and associated benefits for human well-being. Understanding how urban residential green spaces have evolved can help improve sustainable urban planning and design, but it requires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…We collected data through household and yard surveys via a convenient-based recruitment at six permanent monitoring locations within the Río Piedras Watershed (RPWS) based on the San Juan Urban Long-Term Research Area (ULTRA) Collaborative Network stratified sampling scheme [31,34,86,98]. The six sites have been studied to address a variety of social-ecological questions at residential scales since 2011 [26,30,31,82,86,98,99] and lie across a rural-urban and elevation gradient of grey coverage (Table 1). At each site a circular buffer zone of 1 km radius was overlaid on aerial photos of San Juan and a street vector file of access roads using ArcGIS v. 9.3 software [100].…”
Section: Sampling Designmentioning
confidence: 99%
See 2 more Smart Citations
“…We collected data through household and yard surveys via a convenient-based recruitment at six permanent monitoring locations within the Río Piedras Watershed (RPWS) based on the San Juan Urban Long-Term Research Area (ULTRA) Collaborative Network stratified sampling scheme [31,34,86,98]. The six sites have been studied to address a variety of social-ecological questions at residential scales since 2011 [26,30,31,82,86,98,99] and lie across a rural-urban and elevation gradient of grey coverage (Table 1). At each site a circular buffer zone of 1 km radius was overlaid on aerial photos of San Juan and a street vector file of access roads using ArcGIS v. 9.3 software [100].…”
Section: Sampling Designmentioning
confidence: 99%
“…Within the Río Piedras Watershed (RPWS), residential yards vary in the amount of green and tree cover [86], found to be partly associated with variation in yard size, with some differences moderately explained by housing tenure, age, and geographic location [34]. Considering these factors have not been able to explain all the variation in yard vegetation cover, one hypothesis is that these associations are also partly driven by differential attitudes toward residential vegetation and their services across social groups and sites within the watershed [31,85]. At least two studies conducted in the San Juan Metropolitan Area (SJMA) of Puerto Rico have shown that while urban dwellers are able to identify many of the ecosystem services provided by urban green infrastructure, green spaces may also generate disservices [81,82].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, such as with Playas Pa'l Pueblo, researchers needed to make physical contact with participants in order to request and interview. The interview question guide was prepared incorporating questions from a previous study conducted by the US National Science Foundation funded project San Juan ULTRA-Ex (Urban Long Term Research Area, Exploratory) and other sources (Muñoz-Erickson, 2014b;Muñoz-Erickson et al, 2016;Meléndez-Ackerman et al, 2016). The question guide contains five main sections: background questions on the individual being interviewed and the organization she represents, access to information on community environmental risks, their attitudes toward current livability in San Juan, the perceived capacity for community innovation and change, and a closing section that provides participants the opportunity to add anything to the interview that was not previously covered.…”
Section: Methodsmentioning
confidence: 99%
“…Meléndez-Ackerman et al [49] examines residential yard management choices in San Juan, which is starting to exhibit shrinking in some neighborhoods. The differences in how residential landscapes are managed in occupied lots across regions may indicate a potential for differences in how vacant land is managed as well.…”
Section: Synopsis Of Contributionsmentioning
confidence: 99%